Irritable Bowel Syndrome and Gastrointestinal Parasite Infection in a Developing Nation Environment - Douglas R. Morgan; Matthew Benshoff; Mercedes Cáceres; Sylvia Becker-Dreps; Loreto Cortes; Christopher F. Martin; Max Schmulson; Rodolfo Peña (Gastroenterology Research and Practice)
Postinfectious IBS is defined in the industrialized world as IBS onset following a sentinel gastrointestinal infection. In developing nations, where repeated bacterial and parasitic gastrointestinal infections are common, the IBS pathophysiology may be altered. Our aim was to investigate the relationship between intestinal parasite infection and IBS in the “nonsterile” developing world environment. IBS subjects were identified from a population-based sample of 1624 participants using the Rome II Modular Questionnaire. Stool samples from cases and randomly selected controls were examined for ova and parasites. Logistic regression models explored the relationship between IBS and parasite infection. The overall IBS prevalence among participants was 13.2% (9.3% males, 15.9% females). There was no difference in parasite carriage between IBS cases and controls, 16.6% versus 15.4% (P=0.78), nor among IBS subtypes. The pathophysiology of post-infectious IBS may be altered in the developing world as compared to industrialized nations and warrants investigation.